Tourism Opportunities for Kazakhstan on the Great Silk Road (Journal of Geography and Environmental Management, 2018)
Kazakhstan is a big country in central Asia. The Great Silk Road is one of the reasons people must visit the country because Kazakhstan was one of the key countries that participated in it. Nowadays, the history comes back again and the country is planning to become a destination that will be home for international and domestic tourists. Astana intends to invest $10 billion, $6 billion of which will come from private investors, and the country’s tourism planners hope that it will help to develop its tourism sector by 2020. For centuries, crowds of people speaking diverse languages filled the bazaars of Asia, and long caravans crept along dusty roads carrying precious gems and silks, spices and dyes, gold and silver, and exotic birds and animals to Europe. Yet the Silk Road was to become not only a great trade route but the melting pot of two very different civilizations; those of the East and the West, with their specific cultural traditions, religious beliefs, and scientific and technical achievements. Central Asia, situated between China and India in the east, bordering on the European world in the west, spreading between the Volga and Siberia in the north, and between Persia and Arabia in the south, for almost two thousand years stood at the crossroads of the world’s great civilizations and cultures. Kazakhstan’s tourism officials have expressed their desire to attract more international travelers. However, tourism planning needs something more than just money to attract tourists from targeted countries. A complicated visa and registration process is one obstacle already being addressed. Kazakhstan is hardly working on it, including the visa free access for Central Asian countries who participates in the Silk Road project. The Silk Road Action Plan 2016/2017 a comprehensive overview of UNWTO’s strategies and initiatives designed to help Silk Road tourism grow more robust, competitive and sustainable is being researched. It can become one of the tools that will push further the development of Silk Road